Uncertainty shocks and employment fluctuations in Germany: The role of establishment size - Tim Kovalenko (Friedrich-Alexander-Universität Erlangen-Nürnberg, 2021)
Uncertainty shocks are found to adversely affect labor market outcomes. Most studies attribute labor adjustments costs for the propagation of macroeconomic uncertainty to the labor market. Given that large establishments in Germany face higher labor adjustments cost, they should be affected more strongly by these shocks. Therefore, this paper studies the effects of uncertainty shocks on employment adjustments in large and small establishments employing four structural vector auto-regressive models with quarterly data for Germany in the period 1991-2014. These four models estimate effects of uncertainty shocks on employment, worker flows, job flows as well as worker churn, both for establishments with less than 100 and with at least 100 employees. The results suggest that uncertainty shocks induce considerable employment fluctuations in large establishments, while they have barely an effect on small establishments. Furthermore, large establishments adjust their labor input in response to an uncertainty shock by delaying the replacement of workers who leave these establishments.
Keywords: E24; E32; J63; 330; Uncertainty Shocks; Employment; Worker Flows; Job Flows; Worker Churn; Establishment Size; Structural Vector Auto-Regression; Germany